PO43− Coordinated Robust Single‐Atom Platinum Catalyst for Selective Polyol Oxidation. (23rd March 2022) - Yan, Hao; Zhao, Mingyue; Feng, Xiang; Zhao, Siming; Zhou, Xin; Li, Shangfeng; Zha, Minghao; Meng, Fanyu; Chen, Xiaobo; Liu, Yibin; Chen, De; Yan, Ning; et al.
Abstract: Achieving efficient catalytic conversion over a heterogeneous catalyst with excellent resistance against leaching is still a grand challenge for sustainable chemical synthesis in aqueous solution. Herein, we devised a single‐atom Pt1 /hydroxyapatite (HAP) catalyst via a simple hydrothermal strategy. Gratifyingly, this robust Pt1 /HAP catalyst exhibits remarkable catalytic selectivity and catalyst stability for the selective oxidation of C2 –C4 polyols to corresponding primary hydroxy acids. It is found that the Pt−(O−P) linkages with strong electron‐withdrawing function of PO4 3− (Pt1 −OPO4 3− pair active site) not only realize the activation of the C−H bond, but also destabilize the transition state from adsorbed hydroxy acids toward the C−C cleavage, resulting in the sharply increased selectivity of hydroxy acids. Moreover, the strong PO4 3− ‐coordination effect provides electrostatic stabilization for single‐atom Pt, ensuring the highly efficient catalysis of Pt1 /HAP for over 160 hours with superior leaching resistance. Abstract : A single‐atom Pt1 /hydroxyapatite (HAP) catalyst is successfully synthesized by a simple and green hydrothermal strategy. Benefiting from the strong PO4 3− ‐coordination effect, Pt1 /HAP exhibits outstanding catalytic selectivity and catalyst stability without Pt leaching for the selective oxidation of C2 –C4 polyols to corresponding primary hydroxy acids over long periods of operation (>160 h).